Bordetella pertussis exhibits genomic diversity within patients and laboratory culture - E. Bouda; Y. Peng; M. M. Williams; P. K. Cassiday; T. H. Skoff; H. Ju; H. Fueston; D. Kurien; D. Morales; M. Cole; E. A. Travanty; D. Santoro; et al. (mSystems)
ABSTRACT Over the past decade, genomic characterization of Bordetella pertussis isolates recovered from US pertussis patients has unveiled noteworthy structural gene order variations. Whole-genome sequencing (WGS) shows that although B. pertussis exhibits little gene sequence variation, genomes from clinical isolates frequently differ in gene order through rearrangement between insertion sequence elements. To better understand rates of genome rearrangement and single nucleotide polymorphism (SNP) in B. pertussis, intra-patient genomic diversity was examined. Five states submitted, on average, five isolates per patient specimen following culture confirmation to the US Centers for Disease Control and Prevention for molecular characterization. Analysis of 149 patient specimen sets revealed only rare SNP variation, while isolate sets from 12 patients included genomic rearrangements that did not impact vaccine antigen production. To investigate the frequency and stability of such rearrangements during laboratory culture, replicate cultures of two pairs of isolates differing by duplication and inversion were subcultured for eight serial passages. WGS confirmed the initial presence of rare duplication mutations that became dominant in later passages, as well as the stable maintenance of a large, inverted genomic region during passage. These findings suggest that B. pertussis exhibits genomic diversity within a single clinical diagnostic specimen and acquires genomic variations during serial laboratory passages, indicative of bacterial genomic plasticity. Importantly, these rearrangements did not impact the frequency or distribution of SNPs. These results underscore the importance of minimizing the laboratory passaging of clinical isolates used for infectious disease surveillance.IMPORTANCEThe whooping cough-causing bacterium Bordetella pertussis can alter its genetic structure while conserving areas essential for vaccine efficacy. By examining B. pertussis from infected patients, we demonstrate the significance of reducing laboratory manipulation of bacteria to maintain reliable monitoring data from laboratory cultures. Public health officials can use these data to develop efficient disease control tactics and better understand B. pertussis’s adaptability. This study highlights the importance of immunizations and the necessity of thorough genetic surveillance in the fight against this chronic and avoidable respiratory illness.